(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study investigates the effect of tax avoidance strategies on corporate social responsibility (CSR) initiatives and firm performance across industries. Using a systematic literature review (SLR) approach, we analyze 34 relevant studies from various academic databases. The findings suggest that the relationship between tax avoidance and CSR is complex and influenced by industry context, tax regulations, and social pressures. Firms engaging in aggressive tax avoidance tend to increase CSR spending to maintain social legitimacy and reduce reputational risk. However, the impact of tax avoidance on firm performance varies, with potential short-term positive effects offset by long-term reputational and litigation risks. This study provides important insights for managers, regulators, and stakeholders in designing balanced tax and CSR strategies to enhance corporate sustainability.